A new trochoidal toolpath in milling operations - Kiyak, Murat; Emiroglu, Ugur; Bastekeli, Orhun (YILDIZ TECHNICAL UNIV, 2023)
The milling is a widely used method in the manufacturing industry, especially in the production of complex engravings such as die & molds. Rough milling often requires a large material removal rate in a short time. This purpose also requires the selection and use of the best milling tool path. Today, trochoidal milling is receiving more attention than conventional milling, especially as it significantly increases tool life. In this study, a new toolpath model for trochoidal milling is suggested and this proposed toolpath model is examined in terms of cutting temperature, cutting force, surface quality, tool wear. In this new trochoidal toolpath model proposed for the milling method, the cutting force did not change much compared to the standard trochoidal tool path, but better surface quality and less tool wear were observed.
Keywords: Trochoidal Milling; Toolpath; Temperature; Surface Quality; Cutting Force; Tool Wear; Thermodynamics